Biocatalytic desulfurization of thiophenic compounds and crude oil by newly isolated bacteria - Mohamed, Magdy El-Said; Al-Yacoub, Zakariya H.; Vedakumar, John V. (Frontiers in Microbiology, 2015)
Microorganisms possess enormous highly specific metabolic activities, which enable them to utilize and transform nearly every known chemical class present in crude oil. In this context, one of the most studied biocatalytic processes is the biodesulfurization (BDS) of thiophenic sulfur-containing compounds such as benzothiophene (BT) and dibenzothiophene (DBT) in crude oils and refinery streams. Three newly isolated bacterial strains, which were affiliated as Rhodococcus sp. strain SA11, Stenotrophomonas sp. strain SA21, and Rhodococcus sp. strain SA31, were enriched from oil contaminated soil in the presence of DBT as the sole S source. GC-FID analysis of DBT-grown cultures showed consumption of DBT, transient formation of DBT sulfone (DBTO2) and accumulation of 2-hydroxybiphenyl (2-HBP). Molecular detection of the plasmid-borne dsz operon, which codes for the DBT desulfurization activity, revealed the presence of dszA, dszB, and dszC genes. These results point to the operation of the known 4S pathway in the BDS of DBT. The maximum consumption rate of DBT was 11 µmol/g Dry Cell Weight (DCW)/h and the maximum formation rate of 2-HBP formation was 4 µmol/g DCW/h. Inhibition of both cell growth and DBT consumption by 2-HBP was observed for all isolates but SA11 isolate was the least affected. The isolated biocatalysts desulfurized other model DBT alkylated homologs. SA11 isolate was capable of desulfurizing BT as well. Resting cells of SA11 exhibited 10% reduction in total sulfur present in heavy crude oil and 18% reduction in total sulfur present in the hexane-soluble fraction of the heavy crude oil. The capabilities of the isolated bacteria to survive and desulfurize a wide range of S compounds present in crude oil are desirable traits for the development of a robust BDS biocatalyst to upgrade crude oils and refinery streams.